2006
DOI: 10.1117/12.644378
|View full text |Cite
|
Sign up to set email alerts
|

Cavity ring-down spectroscopy with a pulsed distributed feedback quantum cascade laser

Abstract: A pulsed distributed feedback quantum cascade laser operating near 970 cm -1 (10.3 µm) was coupled with the technique of cavity ring-down spectroscopy, as described here for the first time. The newly constructed set-up was tested by recording three relatively weak rotational lines of the 10 0 0→00 0 1 vibrational band of CO 2 in the range from 966.75 cm -1 to 971.5 cm -1 . The CO 2 lines were recorded by measuring the decay time of a CO 2 -N 2 mixture flowing through an open sample tube placed between the cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The k values from the ICOS spectrum are below 6 ϫ 10 −5 cm −1 , clearly larger than that obtained from the CRDS analysis but almost a factor of 10 less than expected from a calculation using the HITRAN database ͑2004 edition͒. 61 The two CH 4 Similar observations were made by Sukhorukov et al 49 They concluded that the dual effects of line broadening and line position shifts might be minimized to some extent by reducing the pulse widths used to operate the laser. In our case it is 60 ns and it was found that reducing it lead to an insufficient signal for detection after the cavity.…”
Section: Ch 4 Detection At 742 Msupporting
confidence: 78%
See 4 more Smart Citations
“…The k values from the ICOS spectrum are below 6 ϫ 10 −5 cm −1 , clearly larger than that obtained from the CRDS analysis but almost a factor of 10 less than expected from a calculation using the HITRAN database ͑2004 edition͒. 61 The two CH 4 Similar observations were made by Sukhorukov et al 49 They concluded that the dual effects of line broadening and line position shifts might be minimized to some extent by reducing the pulse widths used to operate the laser. In our case it is 60 ns and it was found that reducing it lead to an insufficient signal for detection after the cavity.…”
Section: Ch 4 Detection At 742 Msupporting
confidence: 78%
“…Possible explanations for the effects observed here can be found in the work of Sukhorukov et al 49 They discussed the deviations in their measurement series ͑i.e., absorption lines with an increased linewidth and shifted line positions with increasing pulse width͒, which were not as pronounced as those presented here, in terms of the well-known frequency-down chirp of the QCL. The seed current for the laser generates heat during the pulse which, in turn, makes the frequency decrease throughout the duration of the laser pulse.…”
Section: B Bandwidth Effects With a Pulsed Qclmentioning
confidence: 70%
See 3 more Smart Citations